Association of Common Medications and the Risk of Early-Onset Gastric Cancer: A Population-Based Matched Study. (2nd December 2021) - MacArthur, Taleen A.; Harmsen, William Scott; Mandrekar, Jay; Abraha, Feven; Grotz, Travis E.
Abstract : Background . Early-onset gastric cancer (EOGC, age ≤ 60 years at diagnosis) now comprises >30% of new gastric cancers in the United States. It is hypothesized that chronic acid suppression with proton-pump inhibitors (PPIs) may promote tumorigenesis, while other medications including statins, nonsteroidal anti-inflammatory drugs (NSAIDs), metformin, and cyclooxygenase-2 (COX-2) inhibitors have been proposed as protective. We aimed to assess for an association between use of the aforementioned commonly prescribed medications and EOGC development. Methods . We used a population-based medical record linkage system, to identify cases of EOGC in Olmsted County, Minnesota, between January 1, 1995, and December 31, 2020. Patients were matched 1 : 1 with controls based on age at diagnosis, sex, smoking status, and body mass index (BMI). Conditional logistic regression was used to examine associations with the odds of EOGC development. Results . Ninety-six cases of EOGC were identified during the study period. On both univariate and multivariate regression analysis, there was no significant association between use of PPIs, statins, NSAIDs, or metformin and EOGC development. In a final multivariable model, there was a significant reduction in odds of EOGC with COX-2 inhibitor use for six months or more prior to cancer diagnosis (OR = 0.39, 95% CI 0.16-0.94). Conclusion . In this retrospective, population-based study of individuals in Olmsted County, MN, we found significantly reduced odds of EOGC development associated with COX-2 inhibitor use for six months or more prior to diagnosis, but no association between EOGC development and use of PPIs and other commonly prescribed medications.